SISTEM INFORMASI GEOGRAFI FASILITAS MASJID DI KELURAHAN JAKASAMPURNA, BEKASI BARAT - M. Achsan Isa Al Anshori; Fatkhurohman Fatkhurohman; Firstiannisa Rizki; Muhammad Farhan (Jurnal Teknik dan Science, 2023)
Geographic Information Systems (GIS) have become an important tool in the management of spatial information in various fields, including religion and belief. Regarding Islamic places of worship, mosques have a central role as centers of worship, community activities, and social. With the increasing role of geospatial technology, the application of GIS in the management and mapping of mosque locations has become an interesting and relevant research area. This abstract discusses the use of GIS technology in the management and mapping of mosque locations. The author outlines how geospatial technology has been used to collect, integrate, and analyze mosque-related data, such as the mosque's geographic location, existing facilities, and other related data. The purpose of this writing is to build a Geographic Information System that can convey information in the form of locations and facilities in the Jakasampurna area mosque.In addition, this paper also considers the benefits of implementing GIS in mosque management and mapping, including management efficiency, community needs analysis, and sustainable development planning.